Tecnologías de energías renovables (TER) desde el compromiso público - Gallego-Torres, Adriana-Patricia; Ballesteros-Ballesteros, Vladimir-Alfonso (Revista Científica, 2021)
This work presents an extensive review about the importance of citizen positions in the implementation of renewable energy technologies (RET). In the last decades, education has tried to understand, from the perspective of public commitment, the social acceptance of renewable energy technologies and the participation of communities in decision-making processes related to the transition towards the implementation of clean energies. In this sense, this study makes a theoretical reflection on public commitment, the acceptance and implementation of renewable energy technology models, and citizen participation.